PENGARUH VARIASI JENIS AIR DAN KONDISI AKTIVASI DARI ADSORBEN ARANG SEKAM TERHADAP PRESTASI MESIN DAN KANDUNGAN EMISI GAS BUANG SEPEDA MOTOR KARBURATOR 4-LANGKAH - Pratama, Dian Eka; Wardono, Herry (Jurnal Ilmiah Teknik Mesin FEMA, 2014)
The fuel crisis is one of the problems that faced by the world and Indonesia today. To reduce the vehicle fuel consumption, it can be done by using charcoal from rice husk pellet. This research is done with some testing that is the runs test (road test and acceleration),stationary and emission testing. Charcoal pellets are packed in a frame and placed in the air filter on the absolute revo 110 cc motorcycle.In this study, the efficient use of water in the mixture of pellet making charcoal is the best zeolite water immersion results (H12Z20),the best activation conditions at a temperature of 150 C and the activation time of 2 hours. The charcoal pellets can save fuel by 15.72% on road test, and making the accelerate for 7.02% and save fuel consumption until 18.55% on a stationary test. Rice husk pellets are also proven to reduce vehicle exhaust emissions. it can reduce levels of CO and HC by 85,71% at 37,45%  as well as increasing levels of CO  by 6,70%.Keywords : performance, rice hulk charcoal pellets, charcoal adsorbent pellets, exhaust emissions.